P53/Lactate dehydrogenase A axis negatively regulates aerobic glycolysis and tumor progression in breast cancer expressing wild‐type p53. Issue 3 (31st January 2019) - Zhou, Yao; Niu, Weihong; Luo, Yanwei; Li, Hui; Xie, Yong; Wang, Heran; Liu, Yukun; Fan, Songqing; Li, Zheng; Xiong, Wei; Li, Xiaoling; Ren, Caiping; et al.
Abstract : Tumor suppressor p53 is a master regulator of apoptosis and plays key roles in cell cycle checkpoints. p53 responds to metabolic changes and alters metabolism through several mechanisms in cancer. Lactate dehydrogenase A (LDHA), a key enzyme in glycolysis, is highly expressed in a variety of tumors and catalyzes pyruvate to lactate. In the present study, we first analyzed the association and clinical significance of p53 and LDHA in breast cancer expressing wild‐type p53 (wt‐p53) and found that LDHA mRNA levels are negatively correlated with wt‐p53 but not with mutation p53 mRNA levels, and low p53 and high LDHA expression are significantly associated with poor overall survival rates. Furthermore, p53 negatively regulates LDHA expression by directly binding its promoter region. Moreover, a series of LDHA gain‐of‐function and rescore experiments were carried out in breast cancer MCF7 cells expressing endogenous wt‐p53, showing that ectopic expression of p53 decreases aerobic glycolysis, cell proliferation, migration, invasion and tumor formation of breast cancer cells and that restoration of the expression of LDHA in p53‐overexpressing cells could abolish the suppressive effect of p53 on aerobic glycolysis and other malignant phenotypes. In conclusion, our findings showed that repression of LDHA induced by wt‐p53 blocks tumor growth and invasion through downregulation of aerobic glycolysis in breast cancer, providing new insights into the mechanism by which p53 contributes to the development and progression of breast cancer. Abstract : In the present study, we analyzed the association and clinical significance of wt‐p53 and LDHA expression in breast cancer with wt‐p53 expression and explored the mechanism of p53 regulation of LDHA at the transcription level. Furthermore, we carried out rescue experiments to identify the functional role and molecular mechanism of wt‐p53 and LDHA in breast cancer in vitro and in vivo. In summary, our findings show that p53 can directly regulate the expression of LDHA at the transcriptional level to control aerobic glycolysis, cell growth and invasion in breast cancer.